The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.14393/bj-v31n3a2015-22431
|View full text |Cite
|
Sign up to set email alerts
|

Demanda energética de diferentes manejos de solo no cultivo de milho

Abstract: RESUMO:O balanço energético permite identificar as possíveis entradas e saídas de energia no processo de produção, resultando no saldo energético final do processo produtivo. O objetivo do presente trabalho foi avaliar os fluxos de energia de diferentes sistemas de cultivo para produção de milho na região de Lavras-MG. Foi realizado o estudo da eficiência energética e o balanço energético quantificando-se o coeficiente energético de cada componente envolvido no processo de produção e se determinaram as matrize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…It was possible to observe a strong predominance of direct energy consumption (42,357.67 and 43,118.56MJ ha -1 ) in comparison to the indirect one (3,286.18 and 4,185.04MJ ha -1 ). Most of the authors that used a similar energy classification also reported a greater influence of direct energy in their energy matrix (ANGONESE et al, 2006;BIAGGIONI;BOVOLENTA, 2010;CUNHA et al, 2015;MARTINS et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It was possible to observe a strong predominance of direct energy consumption (42,357.67 and 43,118.56MJ ha -1 ) in comparison to the indirect one (3,286.18 and 4,185.04MJ ha -1 ). Most of the authors that used a similar energy classification also reported a greater influence of direct energy in their energy matrix (ANGONESE et al, 2006;BIAGGIONI;BOVOLENTA, 2010;CUNHA et al, 2015;MARTINS et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…According to the soil fertility analysis, the recommended dosage of NPK was smaller in the second harvest, which reduced the demand of fertilizers. Several authors that performed the energy balance of maize crop for grain and silage presented the fertilizers as the main input of energy consumption (CUNHA et al,2015;MARTINS et al,2015;VEIGA et al,2015;LIN et al,2016;FERRO et al,2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A eficiência energética foi obtida pela razão entre a quantidade de energia total de saída e o consumo total de energia durante Introduction Energy efficiency (EE) is the ratio between the total energy produced by a crop (MJ ha -1 ) and the fossil energy consumed in its production (MJ ha -1 ). Thus, the EE assessment of Brazilian agriculture aims to determine the bottlenecks of the cultivation systems adopted and to identify technologies and energy-saving inputs, especially those of fossil origin, such as fuel, fertilizer, agricultural pesticides, machinery and implements (CAMPOS; CAMPOS, 2004;CUNHA et al, 2015). The EE calculation is a tool for analyzing the economic and environmental sustainability of agricultural production systems.…”
Section: Introductionmentioning
confidence: 99%